The Impact of Poverty on Crime Rate in Sokoto State, Nigeria - Jack, Jonathan; Jackson, Isaac (Kashere Journal of Politics and International Relations, 2025)
Poverty in Sokoto State has contributed to some forms of crimes which have disrupted the relative peace enjoined by the citizens. The aim of the study is to examine the impact of poverty on crime rate in Sokoto State. The study focused on six (6) Local Government Areas (LGAs) across the three (3) senatorial districts where poverty is prevalent in the State. Qualitative method of data collection was employed to capture relevant facts from existing literature, while quantitative method was used to collect data from respondents on the field. This has help in addressing the research objectives which includes identifying drivers of poverty, examining the dimensions of poverty and appraising the impact of poverty on crime rate in Sokoto State. The research adopted structural functionalism theory, which explained that the inability of the systems to provide education, healthcare services, security, job opportunities etc. leads to poverty, hence increase crime rate in the society. The study finds out that the high rate of unemployment constitutes the major driver of poverty in the State, while the citizens suffered educational deprivation as a form of poverty dimension. Findings from the study revealed that out of the numerous crimes committed due to poverty in Sokoto State, assault becomes more prominent. The research therefore recommended; that the State government should embark on massive industrialization programme in order to provide job opportunities for the teaming unemployed youths.